The utility of Glaucoma Information Cards for grasping glaucoma subtypes: a single-center pilot study - Yukinori Yamada; Tetsuya Murase; Emiko Mashida; Yuki Kakeda; Yuuka Shibata; Hiroaki Matsuo (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background In Japan, anticholinergic drugs were contraindicated for glaucoma, regardless of subtype. The contraindication in patients with open-angle glaucoma (OAG) led to excessive medication restrictions because anticholinergic drugs are associated with a low risk of acute glaucoma attacks in OAG. To eliminate this problem, the contraindications of anticholinergic drugs were reduced for types from all glaucoma to angle closure glaucoma (ACG) in 2019. This change requires differentiation of OAG from ACG for the proper use of drugs. The Japan Ophthalmologists Association created Glaucoma Information Cards to share glaucoma subtypes and restricted the medication list. However, only a few studies have investigated the efficacy of Glaucoma Information Cards. In this study, we evaluated the benefits of identifying glaucoma subtypes prior to admission by distributing Glaucoma Information Cards to patients through pharmacists. Methods Pharmacists distributed Glaucoma Information Cards to patients whose glaucoma subtype was unclear at the time of the preadmission pharmacist interview and asked them to have the treating ophthalmologist fill out the glaucoma subtype data. We collected patient data, hospitalized clinical department, status of realization of glaucoma subtypes, methods of realization of glaucoma subtypes, and usage of anticholinergic drugs from medical records. Results First, we investigated how hospital pharmacists identify the type of glaucoma. Pharmacists were able to determine the glaucoma type of most patients through medical records, patient interviews, and the Glaucoma Information Card. We analyzed the records of patients who were scheduled for ophthalmology visits prior to admission and had been given Glaucoma Information Cards. Eleven of the 13 patients brought the Glaucoma Information Card to the hospital, which was analyzed by an ophthalmologist. Two patients were administered anticholinergic drugs without restriction because of proven OAG according to the Glaucoma Information Card. One patient was administered cibenzoline for atrial fibrillation. Another patient received isosorbide dinitrate for coronary angiography. These cases indicate that the distribution of Glaucoma Information Cards can help avoid unnecessary medication restrictions in patients with OAG. Conclusions Our results suggest that the distribution of the Glaucoma Information Cards is useful for proper drug use in patients with glaucoma.